Comparative efficacy of visual inspection with acetic acid versus cytology for cervical cancer screening in Ogbomoso, Nigeria (2017)
Screening test for cervical cancer using visual inspection with acetic acid (VIA) has been advocated by World Health Organization as a suitable, low cost and feasible alternative modality for control of cervical cancer in resource-poor settings as compared to cytological and colposcopic screening. The need for reproducibility, accuracy and comparable efficacy will influence the acceptability of VIA as primary screening modalities for cervical cancer. Methods: A cross–sectional comparative study conducted at BUTH. Data were obtained from 318 consenting women aged 30–65 years using a systematic random sampling method and an interviewer–administered structured questionnaire. Pap smear samples were taken followed by visual inspection with acetic acid. Using Statistical Package for Social Sciences (SPSS) version 23.0, Frequencies were obtained and Chi-square test (X2 ) was used to compare rates and proportions with the level of statistical significance set at less than 0.05. Results: Positive results for premalignant cervical lesion was 1.3% and 4.1% for VIA and Pap smear respectively (X2=4.52; p=0.034). The sensitivity of VIA was 7.7% with positive predictive value of 25% while specificity was 99.0% with a negative predictive value of 96.2%. The prevalence of abnormal cervical lesion in the population studied was 4.1% (95% CI 2.2% – 6.9%). Conclusions: The detection rate for pre-cancerous lesions of the cervix using VIA was significantly lower than that of Pap smear in this study. There may be needed to exercise caution in adopting VIA as primary screening modality for cervical cancer.